MARITIME AUTONOMOUS SURFACE SHIP (MASS) DAN STUDI NORMATIF TERHADAP TANGGUNG JAWAB NEGARA BENDERA DALAM HUKUM LAUT INTERNASIONAL - Rahma, Moli Aya Mina (Jurnal Ilmiah Advokasi, 2025)
Technological advances in the maritime sector have shifted applications from manned ships to Marine Autonomous Surface Ships (MASS) as a form of marine management for international marine innovation. This study aims to analyze the legal status and international regulations on MASS which have long been discussed and how the concept of flag state responsibility in the application of MASS. This study aims to develop international maritime law, especially related to Autonomous Ships. The method in this study is normative research using a statute approach and a literature study approach. In this study it was found that until now there is still a legal vacuum, namely there are no special provisions regulating the application of MASS, but there are several countries such as Japan and Norway that have started to test the application of MASS at the national level. However, in international provisions, there is no convention that discusses the legal status, regulations, and provisions of flag state responsibility related to the MASS Application. Keywords: Marine Autonomous Surface Ships (MASS); Flag State, International Legal Regulations